Comparative study of ocular and generalized myasthenia gravis in a South Korean cohort - Chaerin Kwon; Jeeyoung Oh; Hyun Jin Shin (PLoS ONE, 2026)
Purpose To compare ocular myasthenia gravis (OMG) and generalized myasthenia gravis (GMG) in a South Korean cohort through an integrated analysis of clinical characteristics, diagnostic findings, and treatment patterns. Methods We conducted a retrospective study of 138 patients with myasthenia gravis (98 with OMG and 40 with GMG). Demographic characteristics, ophthalmic symptoms, serologic results, repetitive nerve stimulation test (RNST) findings, thymic pathology, autoimmune comorbidities, and treatment patterns were evaluated. Results GMG patients had a younger age at symptom onset and a higher proportion of females compared with OMG patients. Combined horizontal and vertical diplopia was more frequent in OMG. AChR antibody positivity was significantly higher in GMG than in OMG (92.5% vs. 36.3%), as were abnormal RNST findings (90.0% vs. 23.5%). A modest but statistically significant positive correlation was observed between AChR-Ab titer and the highest CMAP decrement in the overall cohort (r = 0.381, p = 0.011); however, this association was not significant when analyzed separately in OMG and GMG patients. Thymic abnormalities, particularly thymoma, were more common in GMG. Nonsteroidal immunosuppressant use—especially tacrolimus and azathioprine—was significantly more frequent in GMG, whereas corticosteroid use did not differ significantly between subtypes. Among OMG patients, systemic immunotherapy was more frequently administered to those presenting with both ptosis and diplopia than to those with isolated ptosis. Conclusions In this South Korean cohort, OMG and GMG exhibited distinct demographic, serologic, electrophysiologic, and therapeutic profiles. Recognition of these subtype-specific differences may facilitate accurate diagnosis, individualized treatment selection, and improved clinical management.